RAGAM BAHASA SLANG OLEH REMAJA GEN Z PADA MEDIA SOSIAL TIKTOK (KAJIAN SOSIOLINGUISTIK) - Tasyarasita, Aulia Zahra; Duhita, Meira Elok; Yulianti, Wiwik; Yustanto, Henry (Translation and Linguistics (Transling), 2023)
This study is carried out to explore the forms and meanings of slang as a language variation in sociolinguistic used by Gen Z youths on social media TikTok. This research employed a descriptive qualitative method. The data collection technique used observing and note-taking techniques, then the data obtained was analyzed using data reduction methods, data presentation, and drawing conclusions. The data in this study were obtained by scrutinizing to words or phrases that contain slang and are written in videos uploaded on social media TikTok. This study found that there were 20 data containing slang, consisting of eight (8) data which were funny misspelled words, six (6) data which were abbreviated forms, five (5) data which were shortened forms, and one (1) data in the form of injection.